Étude du vécu des femmes d’âge moyen engagées dans une relation de support auprès de leur mere âgée en perte d’autonomie - Joncas, Helene; Deshaies, Gilles (Canadian Journal of Counselling and Psychotherapy, 2011)
This study attempts to identify and conceptualize the various components of the lived through experience of middle-aged women who support their old-aged and nonautonomous mother. It is based on a review of recent literature. The various components of that literature are analysed and discussed in light of experiential data collected during a group counselling workshop realized in an urban area of the Province of Québec. Some implications for further research and the professional practice of counseling are formulated.